Proceedings of the 12th ACM International Conference on Ubiquitous Computing 2010
DOI: 10.1145/1864349.1864372
|View full text |Cite
|
Sign up to set email alerts
|

Ambient influence

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(44 citation statements)
references
References 31 publications
(14 reference statements)
0
44
0
Order By: Relevance
“…Environmental sustainability has become an increasingly popular topic in HCI, where behaviour change interventions have ranged from embedding twinkly lights in the floor to lead people towards taking the stairs (as opposed to the lift) [36], to using ambient light displays to illustrate electricity usage in the work place [23]. The use of sensing and tracking technologies has been particularly prevalent [3], with a focus on developing systems that collect and visualise information e.g.…”
Section: Tracking Energy Usagementioning
confidence: 99%
“…Environmental sustainability has become an increasingly popular topic in HCI, where behaviour change interventions have ranged from embedding twinkly lights in the floor to lead people towards taking the stairs (as opposed to the lift) [36], to using ambient light displays to illustrate electricity usage in the work place [23]. The use of sensing and tracking technologies has been particularly prevalent [3], with a focus on developing systems that collect and visualise information e.g.…”
Section: Tracking Energy Usagementioning
confidence: 99%
“…Miro [1] informed office workers on the overall emotional climate in the building. The Clouds [12] attempted at persuading users to use the stairs instead of the lift. These works inspire our research as they prove that introducing new artefacts to office spaces can benefit the communities of office workers.…”
Section: Related Workmentioning
confidence: 99%
“…They provided powerful motivators and demonstrated approaches of ways in which behavior can be influenced without people noticing. The field study of twinkly lights [Rogers et al, 2010], for example, showed that ambient information could transform the way people behave without them being aware of it, in this case, taking stairs rather than the elevator.…”
Section: Motivating Physical Activitymentioning
confidence: 99%